A low proficiency test of expeditious reading - Naranjo-Escobar, Francisco; Chen, Fan; Czajkowski, Michelle (Lenguas Modernas, 2021)
This project sought to develop a test to assess expeditious reading abilities in low proficiency English learners with Spanish L1, which to the date the project was conducted and to authors’ best knowledge constituted a research gap. To achieve this aim, the team developed a new construct based on the existing literature and extrapolated from current research to fill the gap. Participants were Chilean high school students enrolled in the public education system. Results showed that low proficiency learners can perform expeditious reading operations in their L2. These results, however, must be taken with care as further research is required to reach conclusive results.